Integration of Environmental and Social Cost Accounting into Corporate Strategic Decision-Making - Sonia, Lucya Erlinda (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This systematic literature review synthesizes scholarly research Scopus-indexed publications published between 2019 and 2025 concerning the integration of Environmental and Social Cost Accounting (ESCA) into strategic corporate decision-making. This research objectives are to systematically review, analyze, and categorize the primary internal measurement and reporting frameworks for Environmental and Social Costs used by companies, by which ESCA information is integrated into corporate investment and capital budgeting decisions, enables sustainable supply chain management, influences strategic pricing and market positioning decisions. This study addresses the methodological and conceptual frameworks employed by firms to measure and report non-financial costs and analyzes how this information influences long-term value creation. The findings of this review reveal that ESCA operationalization relies heavily on micro-level management tools, specifically material flow cost accounting and life cycle costing. This refinement internalizes prospective regulatory costs, liability risks, and long-term climate-related cash flow adjustments, effectively transforming financial analysis to meet external ESG reporting demands. The study concludes that the effective integration of ESCA is not merely a compliance task dictated by legitimacy theory but is, fundamentally, a crucial mechanism for securing a sustained competitive advantage, although harmonization challenges and the current focus gap